Bisexuality, Mental Health, and Media Representation. Issue 3 (2nd July 2016) - Johnson, Hannah J.
ABSTRACT: There is a mental health crisis in the bisexual community, and though the issues of mental health and media representation are analyzed separately in bisexual literature, they are rarely put side by side. Media such as television, film, and music often contribute to the perpetuation of negative stereotypes and stigmas about people who are bisexual. How do these issues contribute to the high rates of depression, anxiety, and suicide among individuals who are bisexual? What issues do individuals who are bisexual face when they choose to seek help? This research project contributes to bisexual literature by drawing connections between media representation and mental health by firstly examining existing literature on bisexual issues such as biphobia, bisexual erasure, media representation, and mental health, and secondly discussing the results of an online survey to determine how other people who identify as bisexual feel about media representation and its relationship to the mental health crisis in the bisexual community.